A Prototyping Model for Self-Appraisal Employee Performance Application Development in Cooperative - Bagastio, Shobrun Jamil; Anisa, Gia; Suakanto, Sinung; Kusumasari, Tien Fabrianti (Politeknik Ganesha Medan, 2023)
Employee performance appraisal which is currently still being implemented cannot yet describe transparency. In addition, the process is still manual, which is far from effective. This study aims to develop a web-based employee performance appraisal application system that can increase the transparency of assessments in microfinance cooperatives. The focus is on using self-appraisal techniques to promote transparency in the appraisal process. Transparent assessments are critical to building trust and fairness during performance evaluations. Using the self-appraisal method, individuals can evaluate their own performance, skills, and achievements in a transparent and unbiased manner. This study investigates the process of making an employee performance appraisal system with the prototyping model method as a development method. The findings of this study contribute to existing knowledge about performance evaluation in microfinance services, particularly in relation to self-appraisal techniques, and offer practical insights for organizations wishing to increase the transparency of appraisals through web-based application systems.